Pemilihan Jenis Kegiatan Wisata Dalam Pengembangan Ekowisata Pesisir Pantai Kutang Lamongan - Mukti Ali; Fuquh Rahmat Shaleh (Faculty of Science and Technology University Ibrahimy, 2021)
Indonesia's environmental services and natural resources have great potential both on land and sea, especially for tourism purposes. One of the tourism sectors comes from coastal tourism. The development of coastal tourism areas must lead to a planned development in a comprehensive manner so that optimal benefits can be obtained for the community. The research was conducted in Labuhan village which is one of the coastal villages in Lamongan Regency. The method used was survey and observation methods coupled with closed interviews with questionnaires, while natural parameters were carried out by field observation. The research aims to analyze, choose the right type of tourism activity according to the suitability index of the type of tourism activity on Kutang beach, Labuhan village, Brondong District, Lamongan Regency. Data analysis was done by means of multi criteria analysis. This analysis is developed based on utility theory, with the assumption that a person's total (composite) utility is formed as an aggregate of the many attributes (components) that make up the utility. The type of tourism activity which is categorized as very suitable or feasible to do in the Kutang beach area is in the form of tracking activities with a suitability value of 84% and Safari Photo of 83%. Alternative types of activities (according to condition) are Canoeing with a suitability value of 80%, fishing and culinary 77% and swinging 74%.